Non‐alcoholic fatty liver disease fibrosis score in patients with psoriasis. (4th November 2015) - Gisondi, P.; Barba, E.; Girolomoni, G.
Abstract: Background: Patients with psoriasis are at risk of non‐alcoholic fatty liver disease (NAFLD) and likely liver fibrosis. Objective: Investigate the prevalence of NAFLD in patients with psoriasis and measure their risk of liver fibrosis. Method: One hundred and twenty‐four patients with psoriasis and 79 healthy controls were included in this cross‐sectional study. NAFLD was diagnosed in the presence of characteristic sonographic features of fatty liver after excluding other secondary causes of chronic liver disease. NAFLD fibrosis score (NAFLD‐FS) was scored in those with NAFLD to measure the risk of advanced liver fibrosis. Results: Prevalence of NAFLD was greater in patients with psoriasis than in controls (44% vs. 26%, P < 0.001). NAFLD‐FS was higher in patients with psoriasis than in controls, suggesting a higher risk of liver fibrosis in those with psoriasis (−1.57 ± 1.4 vs. −3.10 ± 1.5, mean ± SD, P < 0.0001). Psoriasis resulted in a significant predictor of advanced liver fibrosis independently of age, sex, BMI, hypertension and diabetes in the multivariate analysis. Conclusions: Patients with psoriasis should be screened for common causes of liver disease, including NAFLD and liver fibrosis.